2017
DOI: 10.1088/1361-6587/aa5902
|View full text |Cite
|
Sign up to set email alerts
|

Global anomalous transport of ICRH- and NBI-heated fast ions

Abstract: By taking advantage of the trace approximation, one can gain an enormous computational advantage when solving for the global turbulent transport of impurities. In particular, this makes feasible the study of non-Maxwellian transport coupled in radius and energy, allowing collisions and transport to be accounted for on similar time scales, as occurs for fast ions. In this work, we study the fully-nonlinear ITG-driven trace turbulent transport of locally heated and injected fast ions. Previous results indicated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Therefore, the distribution exhibits a ‘bump-on-tail’ similar to what was previously observed (Wilkie et al. 2016, 2017). In order for this inversion to be observable, this maximum must be well separated from the helium ash population.…”
Section: Benchmarking and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, the distribution exhibits a ‘bump-on-tail’ similar to what was previously observed (Wilkie et al. 2016, 2017). In order for this inversion to be observable, this maximum must be well separated from the helium ash population.…”
Section: Benchmarking and Discussionsupporting
confidence: 85%
“…Previous studies (Wilkie et al 2017) found that the D rv , D vr and D vv coefficients play a sub-dominant role compared to radial diffusion (D rr ) at high energy, so this will be the † Here, nα refers to the density of helium that is not Maxwellian ash so that the total helium density is nHe = n ash + nα only transport term kept from Eq. (1.1).…”
Section: Model Distribution Functionmentioning
confidence: 99%
“…The PHS is unfolded into a NES, which contains information on the fast ion distribution. The deconvolution is performed using two codes, both based on the maximum entropy ansatz: the MAXED code [23] and the Deconvolution method with Adaptive Kernel (DAK) [24]. In Fig.…”
Section: Energetic Tails In Pulse Height Spectra and Neutron Emissionmentioning
confidence: 99%
“…The different types of fast ions are characterized by whether their strong radial variation is one of particle density ("NBI-like") or energy density ("ICRH-like"). It has previously been shown that these different classes of fast ions respond differently to turbulence when passive [54,27]. It is worth examining to what extent their effect on turbulence differs compared to their respective dilution effects.…”
Section: Differentiating Classes Of Fast Ionsmentioning
confidence: 99%
“…This is a generalization of the dilution model presented in Ref. [27], which did not include the kinetic effect of fast ions approximated by R 0f . It is also analogous to the τ parametrization used in Ref.…”
Section: Effective Parameter Modelmentioning
confidence: 99%